KUALITAS PELAYANAN PERGANTIAN STNK 5 TAHUN DI SAMSAT CIBADAK KABUPATEN SUKABUMI - Ahmad Danial Fahad; Beddy Iriawan Maksudi; Ginung Pratidina (LPPM Universitas Djuanda Bogor, 2019)
Public service is a form of services provided by the bureaucracy or government to the community as the service user. Implementation of the public service is intended to fulfill the needs in accordance with the wants and expectations of the community. The purpose of this research is to find out the service quality provided by the civil servants in Samsat Cibadak Sukabumi Regency. The service quality can be measured on five dimensions, namely tangible, reliability, responsiviness, assurance, and empathy. This research uses the descriptive-quantitative methods. The population of this research is 1653 service user community and the sample is 96 respondents. Data is collected by using the observations, interviews and questionaires. Then, data is analysed by using the Weight Mean Score (WMS) to count the mean score. The result of this research indicates that the evaluation of respondents on the service quality in Samsat Cibadak Sukabumi Regency gains the mean score 3.8 categorized as good.Keywords: Bureaucracy, Public Service, Service Quality.